Pemanfaatan Oleoresin Jahe (Zingiber officinale) untuk Mengatasi Kelainan Antioksidan Intrasel Superoxide Dismutase (SOD) Hati Tikus Di Bawah Kondisi Stres - Wresdiyati, Tutik; Astawan, Made; Adnyane, I Ketut Mudite; Prasetyawati, Renny Candra (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2005)
This study was conducted to evaluate the activity of ginger oleoresin (Zingiber officinale) on the intracelluler antioxidant-superoxide dismutase (SOD) in the liver of rats under stress condition. A total of twuenty five Wistar rats were used for this study. They were divided into five groups ; (1)K (control), (2) S (stress), (3)O + S (oleoresin followed by stress), (4) S + O (stress followed by oleoresin and (5) O + S +O (oleoresin followed by stress then oleoresin). The dose of oleoresin is 60mg/Kg/BW/day for seven days. Stress condition was done by five days fasting and smimming for five minutes/day, while drinking water was provided ad libitum to all groups. The results showed that ginger oleoresin significantly decreased malonaldehyde (MDA) and elevated SOD activity. The immunohistochemical evaluation also showed that ginger oleoresin increased the content of copper,zinc-superoxide dismutase (Cu,Zn-SOD) in the liver of rats under stress condition. These effects were showed in the tissues of rats treated by ginger oleoresin before or after stress or combination of both.